2001
DOI: 10.1074/jbc.m104700200
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of Inflammatory Stimuli in Activation-induced Cell Death of Mouse Microglial Cells

Abstract: We have previously shown that mouse microglial cells undergo apoptosis upon inflammatory activation and that nitric oxide (NO) is the major autocrine mediator in this process (Lee, P., Lee, J., Kim, S., Yagita, H., Lee, M. S., Kim, S. Y., Kim, H., and Suk, K. (2001) Brain Res. 892, 380 -385). Here, we present evidence that interferon regulatory factor-1 (IRF-1) and caspase-11 are the essential molecules in activation-induced cell death of microglial cells. The apoptogenic action of inflammatory stimuli such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
32
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(37 citation statements)
references
References 49 publications
5
32
0
Order By: Relevance
“…N9 and rat primary microglial cells were treated with the NO donor S-nitroso-N-acetyl-penicillamine (SNAP). As expected from previous studies, 3,4 this treatment caused cell death in both microglial cell systems. Death was accompanied by Bax and Bak activation (NT exposure (Supplementary data, Figure S6) and activation of caspase-3 (Figure 1f)), suggesting that NO induces microglial apoptosis via the mitochondrial pathway.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…N9 and rat primary microglial cells were treated with the NO donor S-nitroso-N-acetyl-penicillamine (SNAP). As expected from previous studies, 3,4 this treatment caused cell death in both microglial cell systems. Death was accompanied by Bax and Bak activation (NT exposure (Supplementary data, Figure S6) and activation of caspase-3 (Figure 1f)), suggesting that NO induces microglial apoptosis via the mitochondrial pathway.…”
supporting
confidence: 90%
“…Studies have shown that AICD induced by lipopolysaccharide (LPS) and interferon (IFN)g occurs via two pathways, one of them mediated via NO and the other via caspase-11. 3,4 Many aspects of this process, however, remain to be elucidated. We investigated AICD induced by LPS and IFNg in mouse N9 microglia 5 and rat primary microglia.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, the current study clearly demonstrates that following intracortical injection with LPS, there is a significant increase in the levels of IL-13 in the cortex in vivo and that IL-13 is expressed exclusively in activated microglia, but not in astrocytes or in neurons. In marked contrast, expression of IL-13 was not detected even in human pure microglia cultures or in human microglial cell lines in the absence or presence of treatment with LPS (Nagai et al, 2001;Lee et al, 2001). These observations raise the possibility that microglia in culture may not have interactions with other cells and/or the conditions necessary for IL-13 expression when compared to the microglia that exist in vivo.…”
Section: Discussionmentioning
confidence: 88%